DETERMINANTS AND OUTCOME OF SEPSIS AMONG INTENSIVE CARE UNIT PATIENTS OF A TERTIARY CARE HOSPITAL, SOUTHERN INDIA- A RETROSPECTIVE CASE–CONTROL STUDY - DRAGO MELBA BAZEL; LATHA T; CHARLET JASMINE VAZ; LATHA S (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: To assess the determinants and outcome of sepsis among intensive care unit (ICU) patients. Methods: A retrospective case–control design was used to assess the determinants and outcomes of sepsis among the patients hospitalized in the ICU from July 2016 to June 2017. Data were collected from the in-patient records of patients hospitalized in the ICU. The medical records were grouped as cases and controls based on the inclusion criteria and the presence or absence of sepsis. The patient list was prepared using the ICU admission register based on the ICD 10 classification of sepsis. From this list, medical records of 348 sepsis cases and 348 non-sepsis patients (controls) were reviewed. Data were collected using demographic pro forma, sepsis determinants checklist, and outcome determinants checklist. Results: Multivariate logistic regression analysis revealed that the likelihood of patients with pre-existing chronic obstructive pulmonary disease and renal failure developing sepsis was twice higher than those who did not have it. Previous hospitalization, heart disease, and the use of antibiotics were the major contributing factors that contributed to the development of sepsis. Most of the cases had septic shock with multi-organ failure. The control group had a faster rate of recovery, and the highest mortality rate was seen among sepsis patients. Conclusion: In the present study, the various risk factors for the development of sepsis were the presence of specific co-morbidities and multiple devices and catheters, such as central line, urinary catheter, Ryles tube, endotracheal tube, tracheostomy tube, and fulminating infections. Routine surveillance of infectious agents and infection control should be emphasized